Investigations of Thrips tabaci and Aeolothrips intermedius population dynamics in tobacco plantations - Orosz, Szilvia; Bujdos, László; Varga, Lajos; Fekete, Tibor (Acta Agraria Debreceniensis, 2018)
Studies were conducted between 2015 and 2017 with yellow sticky traps in seven tobacco plantations. The purpose was to determine when and in what numbers onion thrips individuals can settle into tobacco plantations. The primary objective of the study was to determine the proper timing of chemical treatments, furthermore, the determination of crucial factors that can influence the population dynamics of Thrips tabaci.